2017
DOI: 10.1039/c6cp07922a
|View full text |Cite
|
Sign up to set email alerts
|

The discrete nature of inhomogeneity: the initial stages and local configurations of TiOPc during bilayer growth on Ag(111)

Abstract: The operation of organic optoelectronic devices relies notably on the bulk properties of compound molecular species, but even more so on the influence of interfaces thereof since it is at the interface where elemental electronic processes take place. Their identification and characterization thereby requires that these critical sections of a device are well defined and can be prepared with low defect density. In this context titanyl phthalocyanine (TiOPc) arises as an excellent candidate that reveals the forma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(65 citation statements)
references
References 30 publications
11
53
1
Order By: Relevance
“…[38] The latter values correspond reasonably well to those reported in the literature for TiOPc monolayers on HOPG and bilayers on Ag(111). The best fit was obtained for a permanent TiO group dipole moment of µ TiO = 0.6 eÅ and a molecular dipole moment of µ TiOPc = 0.4 eÅ for mole cules in the bilayer, with a polarizability of α TiOPc = 100 Å 3 and using a bilayer unit cell area of A uc = 189 Å 2 .…”
Section: Phenomenological Analysis Of Work Function Changessupporting
confidence: 90%
See 2 more Smart Citations
“…[38] The latter values correspond reasonably well to those reported in the literature for TiOPc monolayers on HOPG and bilayers on Ag(111). The best fit was obtained for a permanent TiO group dipole moment of µ TiO = 0.6 eÅ and a molecular dipole moment of µ TiOPc = 0.4 eÅ for mole cules in the bilayer, with a polarizability of α TiOPc = 100 Å 3 and using a bilayer unit cell area of A uc = 189 Å 2 .…”
Section: Phenomenological Analysis Of Work Function Changessupporting
confidence: 90%
“…[38,41] Previous SPA-LEED studies of TiOPc on Ag(111) by Fernández et al have shown that this arrangement results in a POL-phase for the monolayer with a primitive unit cell of A uc = 199 Å 2 , [37] while the bilayer is somewhat compressed and has a unit cell area of 189 Å 2 . [38,41] Previous SPA-LEED studies of TiOPc on Ag(111) by Fernández et al have shown that this arrangement results in a POL-phase for the monolayer with a primitive unit cell of A uc = 199 Å 2 , [37] while the bilayer is somewhat compressed and has a unit cell area of 189 Å 2 .…”
Section: Polar Phthalocyaninesmentioning
confidence: 95%
See 1 more Smart Citation
“…Sample Preparation : The presently used Ag(111) and Au(111) samples were prepared by epitaxial growth of metal onto freshly cleaved and carefully degassed mica substrates under high‐vacuum conditions (typical thickness: 1500 Å). As demonstrated elsewhere, this yielded highly ordered (111) surfaces with atomically flat terraces extending over more than 1000 Å, separated by monatomic steps. For the complementary XRD measurements, also Ag(111) and Au(111) single crystals were used to avoid overlapping diffraction peaks of the mica substrate.…”
Section: Methodsmentioning
confidence: 54%
“…21,22 These latest studies also suggest that the oxygen atom is pointing to the vacuum in the monolayer. Molecules in the second layer grow on top of the first one with the oxygen atom facing towards the surface in order to minimize the dipole-dipole interaction between layers 23 (see Figure 1 for a sketch). The different layer morphologies reveal characteristic molecular arrangements on the surface of Ag(111) ranging from the submonolayer till the completion of the monolayer (ML) and the bilayer formation.…”
Section: Introductionmentioning
confidence: 99%